Impact of the inquiry based-science methodology on learning physics - Rodríguez, H D; Gamboa-Suárez, A A; Avendaño-Castro, W R (Journal of physics. Conference series, 2020)
The stigmatization of natural sciences and mathematics as difficult, boring and non-practical subjects, starting at the secondary levels, has caused an increased disarticulation between the significant learning of physics and the student, this can be reflected in a less development of basic competences, an almost instinctive revulsion of a large number of students towards these subjects and poor results in the tests that are carried out. Reflecting on this situation, we apply the inquiry-based science education. The intervention was carried out in a private calendar B school in the town of Chía, Colombia; Latitude: 4.85, Longitude: -74.05 4° 51′ 0″. The participants were 80 students, the instruments used to collect the information were: class observations, surveys, interviews, an entrance, an exit test and another after the exit test. Two specific inquiry based-science type activities were designed: laboratory practices and the manufacture of a device by the student. These two activities in turn had matrices with defined evaluation criteria to evaluate the impact of the intervention. The students found in the investigation, a much more conducive environment for their learning and in the end the proposal allowed to identify positive impacts of the inquiry based-science as well as not so desired results.